Apakah Penerapan Green Accounting, Environmental Performance Dan Corporate Social Responsibility Berpengaruh pada Profitabilitas? Studi di Perusahaan di Jakarta Islamic Index70 - 'Ainulyaqin, Muhammad Hamdan; Rakhmat, AS; Achmad, LI; Mamun, Sukron; Hidayati, AT; AS; LI; Sukron; AT (ILTIZAM Journal of Shariah Economics Research, 2024)
This study aims to determine the effect of implementing green accounting, environmental performance and corporate social responsibility on company profitability. This research is a quantitative study with an associative approach. The type of data used is secondary data with documentation techniques in taking data in the form of annual reports and sustainability reports in each company. In addition, this research applies literature study in collecting data and theories relevant to the topic of this research problem and then reviewing various literature, such as journals, articles, and previous research.Â  The data analysis method used in this research is descriptive statistics and structural equation modeling (SEM) analysis with the partial least square (PLS) method, all of which are processed in the SmartPLS 4 application. Meanwhile, the object of research is companies listed on the Jakarta Islamic Index 70 (JII70) in 2018-2021. The results of this study indicate that there is an influence between green accounting and environmental performance on company profitability. Meanwhile, there is no influence between Corporate Social Responsibility on company profitability